DIVERSITAS JENIS DAN KEMELIMPAHAN AVIFAUNA DI SUB URBAN KOTA MADIUN BAGIAN BARAT - Bingar Diky Linggarjati; Nurul Kusuma Dewi; Umi Nur Khasanah; Yuliana Yuliana (UNIVERSITAS PGRI MADIUN, 2014)
Sub urban of madiun region is area of the border between urban and rural development which experience a lot of road construction and the settlement. This is resulted in damage to the natural habitat of various species of birds. Damage to vegetation or habitat, caused a change in the adaptability of birds that could potentially affect the abundance of birds. The purpose of the study was to determine the type and abundance of bird in the west of sub urban Madiun. The method used is the encounter rates. Results from observational studies with a total of 75 hours indicates the total number of birds species were more abundant in the morning than the afternoon. The most abundant bird is Collocalia fuciphaga with the amounts 576 and a value of abundance 76.8, There are three species that protected by laws: Alcedo meninting, Cloris todirhamphus, and Aethopyga mystacalis. Eastern region is the highest point meeting of bird observation